Corpse removal increases when honey bee colonies experience high Varroa destructor infestation - van Langevelde, F.; Kiggen, F.; van Dooremalen, C.; Cornelissen, B. (Insectes sociaux, 2020)
High parasite load may increase honey bee mortality, which enhances stimuli for undertaker recruitment in colonies due to the presence of more corpses. However, it is unknown whether colonies exposed to the parasitic mite Varroa destructor (V+ colonies) remove corpses faster compared to colonies with reduced parasite levels (V− colonies). To test this hypothesis, different amounts of dead bees (25 or 100) were added to V+ and V− colonies to increase undertaker’s workload and to monitor the colonies’ undertaking performance (number of corpses removed after fixed time intervals and time until task completion). Until 40 min after adding corpses, V+ colonies had removed more corpses compared to V− colonies, especially when 100 corpses were added. At 100 min after adding the corpses and onwards, the difference between the V+ and V− colonies disappeared. V+ colonies used less time until task completion, especially when challenged to remove 25 corpses. The first efficient undertaking response in V+ colonies may have been caused by more or more experienced undertakers on standby compared to V− colonies, resulting in less total time needed to complete their undertaking task at increased workload. Our study suggests that changes in the division of labour in V+ colonies were not impaired, but we cannot exclude long-term effects for the colony as time spent on undertaking cannot be spent on other tasks. Our study contributes to understanding of social resilience in colonies under high stress and exposed to immediate emergencies.